STRATEGI INDONESIA DALAM MANAJEMEN PERLINDUNGAN PEKERJA MIGRAN INDONESIA DI TAIWAN PASCA NEW SOUTHBOUND POLICY - Ramadhan, Muhammad Zulfikar; Amaliyah, Ridha (SIYAR Journal, 2023)
This paper aims to find out what strategy Indonesia has in managing the protection of Indonesian Migrant Workers (IMW) in Taiwan after the New Southbound Policy. The New Southbound Policy is a Taiwanese economic policy that aims to cooperate and exchange resources in South Asia, Southeast Asia, Australia, and New Zealand countries. This study uses qualitative research with a descriptive approach to examine this issue. The data obtained in this study were obtained through interviews, literature studies, and internet searches. The Special Placement Program to Taiwan (SP2T) scheme is considered a strategy to reduce overcharging and monopolistic practices by private employment agencies. This scheme was opened on a limited basis but was well received by many provinces in Indonesia.